Water Quality Based on Chemical Physics Parameters in Daruba Morotai Island Regency - Vicky Rizky A. Katili; Kismanto Koroy; Mujais Lukman (Sangia Publishing, 2020)
Water quality generally indicates the quality or condition of water associated with a particular activity or need. The influx of organic and inorganic pollution into Daruba waters can cause the water quality meets degradation of biological of function. This reseach aimed to determine the quality analysis of the waters of the Daruba. Sampling was carried out in September to oktober 2020 across five reseach stations,then the result of laboratory of water quality parameters were carried out descriptive. The result measurements and laboratory tests of chemical physics parameters show the condition of Daruba waters based on water quality standards on KEPMEN-LH No. 51 Tahun 2004, most of which have exceeded the water quality standards for marine biota.